Clinical profile and outcome of newly diagnosed children with chronic pancreatitis presenting at a tertiary care hospital in Dakshina Kannada - Anveez Azeez; Anitha S. Prabhu; Gautham Pai (International Journal of Contemporary Pediatrics, 2023)
Background: Acute recurrent pancreatitis (ARP) and chronic pancreatitis (CP) are poorly understood conditions of childhood. Aetiology of CP in children is different from adults, very limited studies are available in pediatric population; hence this study was conducted. Methods: This was a hospital record based retrospective study performed in the department of pediatrics, at Yenepoya medical college hospital, Mangalore. Children from 1 month to 16 years of age were included in this study. Demographic data, clinical details, laboratory parameters, imaging results, and treatment data were collected. The data was tabulated and examined in SPSS software v.24 for analysis. Results: Sixteen children with newly diagnosed CP were included in the study. The median age of children diagnosed with CP was 12 years. Pain abdomen as presenting complaint was observed in all the children diagnosed with CP. All children were residents of Karnataka state. Calcific CP was seen in almost 50% of children. There was no history of tapioca consumption in any child diagnosed with CP. In more than 90% of the children, the aetiology was idiopathic. Conclusions: CP is common amongst children from Karnataka, India. Calcific pancreatitis is a common form of presentation and constituted nearly half of children with newly diagnosed CP in our study. Growth failure and steatorrhea are common complications in children with CP. Aetiology in majority of children with CP in our study was idiopathic, and not related to tapioca consumption. Genetic studies to determine the genetic predisposition for CP in children may play a significant role in future.